Primary cutaneous gamma–delta T cell lymphoma presenting as a leg ulcer in a kidney transplant recipient on hemodialysis: a case report with a literature review - Yuki Oba; Hiroki Mizuno; Shigekazu Kurihara; Daisuke Ikuma; Masayuki Yamanouchi; Tatsuya Suwabe; Katsuyuki Miki; Kei Kono; Kennichi Ohashi; Aya Nishida; Atsushi Wake; Yuki Nakamura; et al. (Renal Replacement Therapy)
Abstract Background Kidney transplantation has long been associated with the incidence of lymphoma. These lymphomas are typically Epstein–Barr virus-associated B cell lymphomas. However, T cell lymphomas occur rarely. Case presentation We present the case of a 57-year-old Japanese man. He underwent a living kidney transplantation twice at age 43 and 46 years. However, the kidney function abolished after 9 years, and he restarted hemodialysis at age 55. After 2 years, an ulcer appeared on his right lower leg. It was not ameliorated but enlarged and became too painful to walk. Skin biopsy diagnosed with primary cutaneous gamma–delta (γδ) T cell lymphoma (PCGD-TCL) on his right leg. PCGD-TCL is one of the highly aggressive lymphomas that express gamma–delta T cell receptor gene arrangement and is difficult to diagnose and treat. He underwent cyclophosphamide 350 mg/m2(50% dose), hydroxydaunorubisin 50 mg/m2, vincristine 1.4 mg/m2, and prednisolone 100 mg/body (CHOP) therapy four times, but these were not effective and caused many complications such as septic febrile neutropenia. Although he decided to undergo amputation of his right leg finally, he died following postoperative cytomegalovirus meningitis. Conclusions This is the first case of PCGD-TCL after kidney transplantation. It shows that the transplanted kidney can lead to lymphoma development, even after the functional loss of the transplanted kidney, and that it is crucial to consider performing the biopsy aggressively for untreatable leg ulcers in hemodialysis patients.